RESPONSE OF GROWTH AND YIELD OF POTATO PLANTS TO ADDITION OF BIOFERTILIZERS ,NILE FLOWER PEAT FERTILIZER AND SPRAYING WITH ITS EXTRACT - A. K. N. Al-Zaidi; M. Z. K. Al-Mharib (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to demonstrate effect of adding some Bio-fertilizers,Nile flower peat fertilizer and spraying with its extract on growth and yield of potato, Tow field experiment at spring and fall season2022 was carried out Horticulture Development Station in the kut district of the Directorate of Agriculture ofWasit Governorate The experiment was implemented using factorial arrangement (4×3×2) within randomized complete block design with three replicates, The First factor included the addition of biofertilizers (M) ,which is M0-without adding , M1- added the Mycorrhizae in an amount of 25 g tuber-1 , M2- added the Trichoderma of 4 gtuber-1 and M3- added Mycorrhizae and Trichoderma fungi together, The second factor included the addition of Nile flower peat fertilizer (N), which is N0- without adding , N1- added 15 mg ha-1 and N2- added 30 mg ha-1 , the third factor included spraying with Nile flower peat fertilizer extract (E), spraying with distilled water(E0) and spraying with extract 2 ml L-1 (E1), The results of the statistical analysis showed the significant increase of biofertilizers in vegetative and yield characteristics as number of aerial stems, leaf area ,leaves chlorophyll content, number of tuber , total yield and percent of carbohydrates in the tubers compared with control (M0(, M3 treatment produced greatest value of this characteristics which reached4.911 ,4.714 stem plant-1, 183.0 ,167.1 dm2plant-1, 198.3,240.8 mg 100g-1, 10.56 , 6.977 tuber plant-1, 57.78, 43.95 Mgha-1 and 18.64 ,19.26%for spring and fall seasons respectively. Organic fertilizer showed significant increase in the above characteristics, N2treatmentproduced greatest value which reached 4.837 ,4.554 stem plant-1, 187.9 ,170.6 dm2plant-1 ,203.3, 244.3mg 100g-1, 11.01 , 7.229 tuber plant-1, 61.61 , 46.42 Mgha-1and 18.53 , 19.55%for spring and fall seasons respectively.